D‐α‐tocopheryl polyethylene glycol 1000 succinate‐containing vehicles provide no detectable chemoprotection from oxidative damage. Issue 7 (28th October 2014) - Baumgart, Bethany R.; Van Vleet, Terry R.; Simic, Damir; Salcedo, Theodora W.; Lentz, Kimberley; Donegan, Michael; Davies, Marc H.; Bunch, Roderick T.; Sanderson, Thomas P.; Lange, Robert W.
Abstract The objective of this study was to evaluate potential protective effects of vehicles containing d‐α‐tocopheryl polyethylene glycol 1000 succinate (TPGS), which may impact nonclinical safety assessments of oxidative processes. This was achieved by evaluating plasma, liver and adrenal gland concentrations of d‐α‐tocopheryl succinate (TS) and d‐α‐tocopherol as well as oxidative status of plasma following oral dosing of TPGS‐containing vehicles, intraperitoneal (IP) dosing of TS or ex vivo treatment of blood with H2O2. Male and female rats were dosed orally with formulations containing 5% or 40% TPGS (70 or 550 mg kg–1 day–1 TS, respectively) for 1 week. A control group was dosed orally with polyethylene glycol‐400 (PEG‐400; no vitamin E) and positive control animals received a single 100 mg kg–1 day–1 IP injection of TS. Whole blood from untreated animals was treated ex vivo with 5 or 50 mm H2O2, with or without TS (0.5, 5, 50 or 500 μm) or ascorbate (1 mm), for 1 h. Oral TPGS treatments did not affect d‐α‐tocopherol concentrations in plasma or adrenal glands and caused only transient increases in liver. Concentrations of TS in plasma, liver and adrenal glands were undetectable in control animals, but increased in all other groups. Oral administration of TPGS did not reduce plasma lipid peroxidation in vivo. Substantially greater TS concentrations used ex vivo (100× greater than in vivo) were also unable to reduce lipid peroxidation in H2O2‐treated whole blood. These results provide evidence that administration of oral TPGS vehicles is unlikely to impact nonclinical safety assessments of pharmaceuticals. Copyright © 2014 John Wiley & Sons, Ltd.